NILAI-NILAI PENDIDIKAN ISLAM PADA SYAIR TARI ZAPIN API DI DESA TELUK RHU KECAMATAN RUPAT UTARA - Mastura, Ami; Darwis, Muhajir (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This Research is motivated by the flow of changes and shifts in cultural values adopted by the community. This change in values certainly give more opportunities to be ignored or even to lose some elements of culture an traditionsin society. This situationwill gradualy cuase people to begin to lose to lose the true meaning contained therein. The purpose of this study was to find out the implementation process and the values of Islamic education in the zapin api dance lyrics in Teluk Rhu village. Rupat Utara distcrit. This study uses the theory of Islamic educational values in poetry, the zapin api dance. This type of research is a qualitative research with a descriptive approach. The result of this study are that there ia a bathing process. Ablution process. Perfrom sunnah prayer 2 cycles of prayer, prepare the location, bathe musical instruments and the calips sleeps with musical instrument, carry out Monday-Thursday fasting and the process of starting a fire, and the value of Islamic education contained in the zapin fire poem is the value of the creed found in the zapin poem chick, down ten about believing in the pillars of faith and the pillars of Islam. The value of worship is found in the stanza of the chick drops ten about praying and performing prayers and purifying oneself. Moral values are found in Siti Fatimah’s verses about being grateful. Social values are found in Abdul Kador Jailani’s verses about leadership